On the coagulation efficiency of carbonaceous nanoparticles - Hou, Dingyu (2021)
In this paper we derived the interaction energy between two spherical nanoparticles from the pair-wise Lennard-Jones attractive and repulsive potentials of the constituent atoms of the two particles, and proposed a coagulation efficiency model based on the average particle kinetic energy and the potential well depth (i.e. the minimum interaction energy) between two colliding particles. To test the performance of this new coagulation efficiency model, we applied it in detailed population balance modelling of soot particle size distributions (PSDs), and found better agreement with the measured PSDs in a benchmark premixed ethylene flame than that using the unit coagulation efficiency, especially in the range of small particles with mobility diameter less than 5 nm. Moreover, the agreement between the computed and the measured primary particle size distribution (PPSD) was also improved with the new coagulation efficiency model.